The Effect of Cooperative Learning Model of Structured Numbered Head (SNH) on The Learning Outcomes of Islamic Religious Education - Amirudin Amirudin (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This research is based on students' habits if given group assignments always rely on other friends. To overcome this, it is necessary to apply a cooperative learning model of the numbered head type structure (structured numbered head), the method used is a descriptive quantitative method using correlation studies with cause and effect study. The population is 355 students (all grade VII students). While sampel 20% or as many as 72 students. Data is collected using questionnaires. Statistical analysis measures use partial tests, normality tests, correlation tests, hypothesis tests and influence tests. The calculation of variable X and variable Y obtained a value of 59.11 and a value of 1.99. Then it can be concluded that >, meaning that the hypothesis that the author proposed is accepted. This means that there is a positive or significant influence between the Structured Numbered Heads (SNH) Type Cooperative Learning Model on the Learning Outcomes of Students of Islamic Religious Education Subjects Class VII SMP Negeri 5 Karawang Karawang Regency. While the calculation of the correlation coefficient of 0.99 can be categorized as a perfect correlation because it is between 0.81 - 1.00. There is a degree of correlation or influence of variable X on variable Y of 0.14. So obtaining the influence of variable X on variable Y by 86% means that there are 14% other factors that can affect the Learning Outcomes of Students of Islamic Religious Education Subjects Class VII SMP Negeri 5 Karawang Karawang Regency.